Exploration of Accountability Practices: A Study of the Secretariat of the House of Representatives - Budi Santoso, Priyo (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2024)
The review explores the significance of the SAKIP System, focusing on the Secretariat General of the Indonesian House of Representatives, examining both practical and theoretical aspects. An accountability index of 67.46 emerged, resulting in a "B" predicate. This finding reveals a notable discrepancy compared to the target of 75.00, highlighting a gap between theoretical frameworks and practical implementation of accountability. The research employs a qualitative descriptive methodology, utilizing a desk study to analyze audit data and interpret the findings. Results emphasize the necessity for a collaborative approach to enhance transparency and accountability in the internal audit process. Such attributes play a vital role in strengthening the virtue of programs or outputs produced through audits. The study suggests that accountability goes beyond formal procedures, representing a dynamic interaction among institutions that can bolster legitimacy in practice. Additionally, it fosters a culture of continuous improvement in Government performance. Ultimately, this research contributes to the discourse on accountability by promoting a more integrated and participatory approach within Government operations.